DNA methylation pattern changes upon long-term culture and aging of human mesenchymal stromal cells - Bork, Simone; Pfister, Stefan; Witt, Hendrik; Horn, Patrick; Korn, Bernhard; Ho, Anthony Dick; Wagner, Wolfgang (Aging cell, 2010)
Within 2-3 months of in vitro culture-expansion, mesenchymal stromal cells (MSC) undergo replicative senescence characterized by cell enlargement, loss of differentiation potential and ultimate growth arrest. In this study, we have analyzed DNA methylation changes upon long-term culture of MSC by using the HumanMethylation27 BeadChip microarray assessing 27 578 unique CpG sites. Furthermore, we have compared MSC from young and elderly donors. Overall, methylation patterns were maintained throughout both long-term culture and aging but highly significant differences were observed at specific CpG sites. Many of these differences were observed in homeobox genes and genes involved in cell differentiation. Methylation changes were verified by pyrosequencing after bisulfite conversion and compared to gene expression data. Notably, methylation changes in MSC were overlapping in long-term culture and aging in vivo. This supports the notion that replicative senescence and aging represent developmental processes that are regulated by specific epigenetic modifications.
Gesehen am 09.02.2023